2020
DOI: 10.36129/jog.32.02.03
|View full text |Cite
|
Sign up to set email alerts
|

The adherence adequacy to antenatal care in alleviating the adverse maternal and neonatal outcomes of Iranian pregnant women: a retrospective-prospective study

Abstract: Background. Low adherence of pregnant women to the content of prenatal care guidelines (PCGs) is one of the most significant issues in obstetrics.Objective. This study aimed to improve the well-being of the mother and fetus by preventing maternal and neonatal complications using the adherence to antenatal care (ANC). Patients and methods. An integrated retrospective-prospective longitudinal study with participating 604 pregnant women was carried out in the Iranian community. A valid researcher-made tool was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Zarean et al [39] stressed taking the ratio of middle cerebral artery parameters to the umbilical artery to gain better results. However, Akolekar et al [40] disagree with their result. Additionally, they discussed how maternal factors like ethnicity, parity, BMI, and gestational age affected the values of PI obtained through Doppler studies.…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 82%
“…Zarean et al [39] stressed taking the ratio of middle cerebral artery parameters to the umbilical artery to gain better results. However, Akolekar et al [40] disagree with their result. Additionally, they discussed how maternal factors like ethnicity, parity, BMI, and gestational age affected the values of PI obtained through Doppler studies.…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 82%
“…Women who had more than 3 antenatal visits had their odds of taking any calcium supplements during pregnancy significantly increased by 6 folds compared with their counterparts with a lesser number of antenatal visits (p-value = 0.000). A higher number of antenatal visits has been associated with better obstetric outcomes [ 28 , 29 ]. The number of antenatal care visits is likely to have increased the probability of better antenatal health education [ 30 ] and probable prescription of calcium by health personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review by OuYang H et al, also indicated a significant association between the depression and GDM among pregnant woman [31]. Antenatal and perinatal care is very important and the studies are evident for a better neonatal and maternal outcomes among those who are adhering to the antenatal care interventions [32]. Successful interventions should be planned to control the depression among the pregnant woman.…”
Section: Table 3: Effect Of Depression On Maternal Outcomesmentioning
confidence: 99%